Social and Psychological Aspects of Environmental Consciousness - DORONINA, Marina V.; SEMENKOVA, Svetlana N.; TABURKIN, Vyacheslav I. (Journal of Environmental Management and Tourism, 2018)
This paper studies methodological ways of formation of sociopsychological aspects of environmental consciousness. To this end, environmental psychology is singled out as the most important sociological factor in the internal structure of environmental consciousness. To clarify this problem, the article conducts a methodological analysis of the subject of environmental psychology, studies its links with values, the information environmental field, the subjective relationship of a person with the natural world, the dependence of environmental psychology on everyday environmental consciousness and cognition. From these systemic positions the subject of environmental consciousness, its place and role in environmental consciousness and environmental culture as a whole is determined.